NiCo2O4 Nanofibers as Carbon‐Free Sulfur Immobilizer to Fabricate Sulfur‐Based Composite with High Volumetric Capacity for Lithium–Sulfur Battery - Liu, Ya‐Tao; Han, Dian‐Dian; Wang, Lu; Li, Guo‐Ran; Liu, Sheng; Gao, Xue‐Ping (Advanced energy materials, 2019)
Both the energy density and cycle stability are still challenges for lithium–sulfur (Li–S) batteries in future practical applications. Usually, light‐weight and nonpolar carbon materials are used as the hosts of sulfur, however they struggle on the cycle stability and undermine the volumetric energy density of Li–S batteries. Here, heavy NiCo2O4 nanofibers as carbon‐free sulfur immobilizers are introduced to fabricate sulfur‐based composites. NiCo2O4 can accelerate the catalytic conversion kinetics of soluble intermediate polysulfides by strong chemical interaction, leading to a good cycle stability of sulfur cathodes. Specifically, the S/NiCo2O4 composite presents a high gravimetric capacity of 1125 mAh g−1 at 0.1 C rate with the composite as active material, and a low fading rate of 0.039% per cycle over 1500 cycles at 1 C rate. In particular, the S/NiCo2O4 composite with the high tap density of 1.66 g cm−3 delivers large volumetric capacity of 1867 mAh cm−3, almost twice that of the conventional S/carbon composites. NiCo2O4 nanofibers serve as carbon‐free sulfur hosts to fabricate sulfur‐based composites with high volumetric capacity based on the high tap density. Furthermore, NiCo2O4 can accelerate the catalytic conversion of soluble intermediate polysulfides by strong chemical interaction, leading to a good cycle stability. Therefore, S/NiCo2O4 composite presents tremendous advantages over conventional S/carbon materials in improving the volumetric capacity and cycle stability.